Предмет: Математика,
автор: arnica1
1,3 (х +20у)- 40 (0,9-х)+63у
Ответы
Автор ответа:
0
1.3(х+20у)-40(0.9-х)+63у=1.3х+26у-36+40х-63у=41.3х+89у-36
Автор ответа:
0
научись считать
Автор ответа:
0
Действительно. Надо больше практике в устном счёте и удержание всего выражения в голове.
Автор ответа:
0
1,3 (х +20у)- 40 (0,9-х)+63у=
=1,3x+26y-36+40x+63y=
=41,3x+89y-36
=1,3x+26y-36+40x+63y=
=41,3x+89y-36
Похожие вопросы
Предмет: Химия,
автор: prokopovi1111
Предмет: Математика,
автор: f5544tg5i8
Предмет: Физика,
автор: liliuyyddsss
Предмет: Алгебра,
автор: Che2000